Contemporary management - Jones, Gareth R.; George, Jennifer M. (McGraw-Hill, 2018)
"Contemporary Management 10e mirrors the changes taking place in today's management practice by incorporating recent developments in management theory and research. It provides vivid, current examples of how managers of companies, large and small, address the challenges and opportunities they face and how they can effectively meet them"--Provided by publisher.